Features of the clinical course of gastroenteritis caused by enteropathogenic Escherichia coli with hemolytic-uremic Gasser syndrome - M. S. Kurmangazin; A. R. Astrakhanov; A. N. Iskakova; G. N. Nurlanova (Clinical Medicine (Russian Journal), 2026)
Enteropathogenic infection caused by Escherichia coli, complicated by hemolytic uremic syndrome (HUS), is rare in adults and is associated with a high risk of severe complications and mortality. We present a clinical case of a 25-year-old patient with acute gastroenteritis complicated by infectious-toxic shock, disseminated intravascular coagulation syndrome, acute kidney injury with anuria, and hemolytic uremic syndrome. The etiological diagnosis was confi rmed by bacteriological stool culture with isolation of enteropathogenic Escherichia coli; tests for salmonellosis and shigellosis were negative. The patient received intensive therapy, including antibacterial treatment, infusion therapy, renal replacement therapy, and correction of coagulopathy. Against the background of comprehensive treatment, gradual recovery of renal function and regression of multiple organ failure were observed. The patient was discharged in satisfactory condition. This case highlights the importance of early diagnosis of hemolytic uremic syndrome in adult patients with severe gastroenteritis and the timely initiation of intensive pathogenetic therapy.